2019
DOI: 10.1097/md.0000000000016217
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of rearfoot medial wedge intervention on balance for athletes with chronic ankle instability

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…The relationship between the foot characteristics and the insole type should be examined in future studies. In contrast, several previous studies reported the effectiveness of a medial heel wedge similar in shape to the one we used [10,[42][43][44][45]. We believe that these findings support our study.…”
Section: Discussionsupporting
confidence: 84%
“…The relationship between the foot characteristics and the insole type should be examined in future studies. In contrast, several previous studies reported the effectiveness of a medial heel wedge similar in shape to the one we used [10,[42][43][44][45]. We believe that these findings support our study.…”
Section: Discussionsupporting
confidence: 84%
“…Some researchers have suggested that increased contact area leads to tactile stimulation and proprioception feedback under the foot and improvement of static balance. [31] We believe that two toe lengths in Egyptian-type toes might induce different strengths of stimulation on plantar receptors and result in greater COP displacement.…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned, depending on the injury extent and management rendered, nearly 70% of patients will experience a subsequent sprain within 1 year of the inciting injury 7,10,25 , with more than half of those patients presenting with residual pain, weakness, instability, and swelling similar to the symptoms experienced with CAI 8 . According to Delahunt et al, patients have a 2-fold risk increase of subsequent injury within 1 year after an index ankle sprain 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that ankle dorsiflexion deficits may result from decreased talocrural joint mobilization 9 , calcaneal valgus, and subtalar joint hypermobility 10,20,21 , which may contribute to a higher propensity for recurrent lateral ankle sprains 8 . These deficits cause changes in normal ankle joint alignment and kinematics, negatively affecting postural stability 9,10 .…”
Section: Biomechanics Of the Ankle And Lower Extremitymentioning
confidence: 99%
See 1 more Smart Citation